Reduction of Thiocyanate Complexes of Fe(III) in the Presence of Activated Carbon - Crouse, Karen Anne; Badri, M. (Universiti Putra Malaysia Press, 1993)
Fe (III) complexed with SCN- was found to be reduced to Fe(II) in the presence of activated carbon. The rate of disappearance of the complex was determined spectro photometrically and was found to be first order with respect to Fe(I1I). The enthalpy and entropy of activation are 100 ± 10 kJ/mole and 14.1 ± 0.8 J/mole-K respectively. Some Fe was found to be adsorbed on the catalyst where the actual reduction was suggested to take place. The accompanying oxidation reaction has been suggested to be mainly that of the thiocyanate ions adsorbed at the positive centres on the catalyst.